Nucleic acid-induced chemokine expression in keratinocytes: Implications for skin inflammation - Judit Danis; Evelyn Kelemen; Fanni Balogh; Kornélia Szabó; Gergely H. Fodor; Éva Ádám; Márta Széll (PLoS ONE, 2025)
Chemokines play an important role in the pathogenesis of skin diseases, such as psoriasis, atopic dermatitis, vitiligo, and alopecia areata. Recently literature data supports the theory that alternatively spliced isoforms of these molecules may serve as potential regulators in these diseases. Since self-derived nucleic acids are main culprits in chronic skin diseases we compared the effects of synthetic RNA- and DNA-induced inflammation on the expression levels of chemokines in human keratinocytes. We found that cytoplasmic nucleic acids are potent inducers of monocyte chemoattractant protein-1 (CCL2), interferon gamma inducible protein-10 (CXCL10) and fractalkine (CX3CL1) mRNA-expression, mainly through NF-κB activation, but the pattern recognition receptors responsible for inducing this activation are still unknown. Alternative splicing of these chemokines in keratinocytes was not detected, suggesting other regulatory mechanisms for chemokine activity.